An existence result for a fractional elliptic system involving (p, q)-Laplacian and critical exponent. Issue 5 (4th May 2023) - Zhang, Aini; Deng, Zhiying
ABSTRACT: This paper is dedicated to studying a fractional elliptic system involving (p, q)-Laplacian and critical exponent. Based upon the Nehari manifold and fibering maps, we prove a nontrivial solution for the problem under the proper conditions.